PERLINDUNGAN HUKUM BAGI BANK TERKAIT PERJANJIAN KREDIT KEPEMILIKAN RUMAH DENGAN PENGIKATAN SURAT KUASA MEMBEBANKAN HAK TANGGUNGAN DISERTAI PERJANJIAN BUY BACK GUARANTEE DI KOTA DENPASAR - Darmawan, Ni Ketut Supasti; Sumardika, I Nyoman; Paramartha, I Nyoman Gede (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 1 No 2 (2016)DO - 10.24843/AC.2016.v01.i02.p07, 2016)
Home ownership credit faciliities are very much needed by the people who have low and medium buying power. In theory, as set forth in Article 1, paragraph (2) of the Regulation of the State Minister of Agrarian Services/Head of National Body for Land Affairs (BPN) No. 4 of 1996, with the binding of SKMHT is only granted to secure certain credits ,i.e. to finance simple ownership , modest homes, condominiums with land area of 200m2 and the building has not more than 70m2. In practice many home ownership credit facilities are granted to buy a house with a land area of more than stated by the provision above. Problems also occurs with the provisions of Article 15 paragraph (1) of UUHT which require SKMHT regarding land rights which are already registred, SKMHT must be followed by the making of APHT as late as 1(one) month. Rights to land that has not been registered, should be followed by creating APHT as late as 3(three) months after the SKMHT is granted in accordance with Article 15 of UUHT paragraph (2). However, in granting Home ownership credit, the provision applied is Article 1, paragraph (2) of the Regulation of the State Minister of Agrarian Services/Head of Nation Body for Land Affairs (BPN) No. 4 of 1996 confirming that SKMHT is not mandatory until the end of the principal agreement. The principle issue in this study is the factors that cause the developer defaults on the SKMHT agreement completed with buy back guarantee and the efforts made by a bank if a developer defaults on yhe agreement of buy back guarantee. Type of research used in this thesis was empirical legal research, which departed from the gap between Government Regulation State Minister of Agrarian Services/Head of Nation Body for Land Affairs (BPN) No. 4 of 1996, and the prevailing reality. The Approach used was a qualitative approach. Primary data collection technique was conducted using the method of taking sample interview with the Non-Random Sampling; secondary data collection was done through the technique of documentary studies and tertiary legal materials in the form of dictionaries and encyclopedias. The results showed that the factors that caused the developer defaults on the agreement of SKMHT equipped with buyback guarantee are internal and external factors. The internal factor is the missue of credit facilities and bad character of developers. External factors that make economic recession are that the bank interest rate jump dramatically, as a result many debitors are unable to pay loans. Efforts made by the bank if a developer defaults on the agreement of buy back guarantee can be an effort in litigation and non-litigation paths. The best solution for creditors is through non-litigation paths.
Keywords: Power of Attorney Imposing Liability Rights (SKMHT), Home Ownership Credit (KPR), Providing Mortgage Deed (APHT)